THE STUDY OF RELATIONSHIP BETWEEN INTERNET ADDICTION AND SELF ESTEEM AMONG UNDERGRADUATE STUDENT IN UNIVERSITY MALAYSIA SARAWAK - LARRY HILMA, MUD (Universiti Malaysia Sarawak (UNIMAS), 2020)
There are many studies conducted between internet addiction and self-esteem globaly. This study is importance because it is one of the things can influence our daily life. This study examines the internet addiction and self-esteem in University Malaysia Sarawak (UNIMAS). The sample consisted of 102 students in University Malaysia Sarawak (UNIMAS). The study utilized an instrumental to measure the internet addiction; namely Internet Addiction Test (IAT) and rosenberg self-esteem scale (RSES). Demographic factors (gender, race, faculty, CGPA, Duration online) were examined too. Google form is a flatform used to collect the data from respondent in eleven Faculty in Universiti Malaysia Sarawak (UNIMAS). Data analysis is an inferential statistic (T-test, Pearson Correlation and Multipl Linear Regression). The result suggests that the level of internet addiction among University Malaysia Sarawak (UNIMAS) is moderate. Moreover, (H1) there is a significant of gender difference in internet addiction in this study. But (H2) there is no statistically significant difference between self-esteem based on gender. (H3) There is no significant relationship between self-esteem and internet addiction and (H4) none of the internet addiction factor has an influences toward selfEsteem. It is recommended that problem of internet addiction should be aware to prevent growing of internet addiction.